Ligand–metal cooperativity in quinonoid based nickel(ii) and cobalt(ii) complexes for catalytic hydrosilylative reduction of nitriles to amines: electron transfer and mechanistic insight. Issue 15 (23rd March 2023) - Paramanik, Krishnendu; Bandopadhyay, Nilaj; Sarkar, Gayetri; Chatterjee, Souvik; Roy, Suvojit; Panda, Subhra Jyoti; Purohit, Chandra Shekhar; Biswas, Bhaskar; Das, Hari Sankar
Abstract : Non-innocent quinonoid ligand based square-planar Ni(ii ) and Co(ii ) complexes showing excellent catalytic activity towards hydrosilylative reduction of nitrile to corresponding primary amine using an inexpensive hydrosilane PMHS. Abstract : The sustainable production of privileged amines by the catalytic reduction of nitriles with an inexpensive silane polymethylhydrosiloxane (PMHS) holds great promise to replace conventional synthetic routes that have limited applicability and involve the use of expensive metal catalysts. The use of late 3d-metal complexes provides an excellent platform for the rational design of inexpensive catalysts with exquisite control over their electronic and structural features through metal–ligand cooperativity. In this context, we have realistically designed two complexes based on nickel(ii ) and cobalt(ii ) with a redox-active imino- o -benzoquinonato ligand. The compounds were characterized by a suite of spectroscopic methods, cyclic voltammetry and single-crystal X-ray diffraction. Both complexes showed excellent catalytic activity in transforming various organonitriles into the corresponding primary amines selectively using the inexpensive PMHS. The catalytic performance of the complexes was evaluated by various control experiments and spectroscopic studies with detailed computational calculations revealing the crucial role of the non-innocent imino- o -benzoquinonato ligand and metal(ii ) ion cooperativity in controlling the reactivity and selectivity of the key metal-hydride intermediates in the course of catalytic reduction.